Antileishmanial Patents Antileishmanial Current Drugs and Relevant Patents - Monzote, Lianet (Recent Patents on Anti-Infective Drug Discovery, 2011)
The World Health Organization has classified the leishmaniasis as a major tropical disease. An effective vaccine is not available and the chemotherapy is the only effective way to treat all forms of disease. Currently, the therapy is toxic, expensive and the resistance has emerged as a serious problem, which has compelled the search for new antileishmanial agents. The aim of this article is to review the recent advances in antileishmanial drugs. In addition, patents from 01/1969 to 12/2009 were analyzed. After initial review, 867 patents were classified as vaccines, immunomodulators and drugs. Among them, the major percent was reached by the drugs, accounting for 68% of the patents. In this review, 580 patents were listed, reviewed and classified according the approach of the inventors in the expansion of antileishmanial drug discovery. In this moment, the scenario of leishmaniasis chemotherapy is more promising than ever. Nevertheless, advances in the understanding of new metabolic pathways and drug targets in the parasite could offer new alternatives to treatment of leishmaniasis.
Keywords: Pneumocystis carinii